DALBACEN cohort: dalbavancin as consolidation therapy in patients with endocarditis and/or bloodstream infection produced by gram-positive cocci - Carmen Hidalgo-Tenorio; David Vinuesa; Antonio Plata; Pilar Martin Dávila; Simona Iftimie; Sergio Sequera; Belén Loeches; Luis Eduardo Lopez-Cortés; Mari Carmen Fariñas; Concepción Fernández-Roldan; Rosario Javier-Martinez; Patricia Muñoz; et al. (BMC, 2019)
Abstract Objectives To analyse the effectiveness of dalbavancin (DBV) in clinical practice as consolidation therapy in patients with bloodstream infection (BSI) and/or infective endocarditis (IE) produced by gram-positive cocci (GPC), as well as its safety and pharmacoeconomic impact. Methods A multicentre, observational and retrospective study was conducted of hospitalised patients with IE and/or BSI produced by GPC who received at least one dose of DBV. Clinical response was assessed during hospitalization, at 3 months and at 1 year. Results Eighty-three patients with median age of 73 years were enrolled; 73.5% were male; 59.04% had BSI and 49.04% IE (44.04% prosthetic valve IE, 32.4% native IE, 23.5% pacemaker lead). The most frequently isolated microorganism was Staphylococcus aureus in BSI (49%) and coagulase-negative staphylococci in IE (44.1%). All patients with IE were clinically cured in hospital; at 12 months, there was 2.9% loss to follow-up, 8.8% mortality unrelated to IE, and 2.9% therapeutic failure rate. The percentage effectiveness of DBV to treat IE was 96.7%. The clinical cure rate for BSI was 100% during hospital stay and at 3 months; there were no recurrences or deaths during the follow-up. No patient discontinued treatment for adverse events. The saving in hospital stay was 636 days for BSI (315,424.20€) and 557 days for IE (283,187.45€). Conclusions DBV is an effective consolidation antibiotic therapy in clinically stabilized patients with IE and/or BSI. It proved to be a cost-effective treatment, reducing the hospital stay, thanks to the pharmacokinetic/pharmacodynamic profile of this drug.